Perancangan Sistem Informasi Penjualan Barang Berbasis Website di Mulya Jaya Putra Meubel Rancaekek - Anjas Trayana; RickyÂ Rohmanto (Syntax Idea)
This research focuses on the design of a web-based information system for selling furniture at Mulya Jaya Putra Meubel, located in Rancaekek, Bandung. The study aims to address the shortcomings in the current sales and promotion strategies. The proposed system encompasses online sales services and product information, aiming to enhance service availability beyond working hours, expand market reach, and provide detailed product information. The study benefits Mulya Jaya Putra Meubel by improving service quality, aids AMIK Al Ma’soem students as a reference, serves as an academic benchmark for the author, and enriches the reader's knowledge.